STRATEGI PENYELESAIAN KONFLIK DALAM ORGANISASI - Mantra, Gede Putu (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The existence of conflicts within organizations is inevitable, conflicts are always present in every life of organizations, whether small organizations or large-scale organizations. It happens, because on the one hand the individuals/groups involved in the organization have different characters, backgrounds and purposes. On the other hand, interdependence is a characteristic of every organization's life. Factors that can influence conflict in the organization's working environment include differences in perception, resource constraints, departmentalization, interdependence, authority relations, roles and expectations, and ambiguity of jurisdiction. Not all conflict is detrimental to the organization, well-organized and well-managed conflict can benefit the organization as a unity. Managing conflict within an organization requires openness, patience and awareness of all parties involved and stakeholders of conflict that occurs within the organization. Some of the methods that are commonly used in managing conflict that occurs in an organizational environment, include: domination, compromise, and integrative resolution.